Effect of cryogenic cooling during grinding of mild steel and stainless steel - Khan, Ahsan Ali; Mridha, Shahjahan; Ali, Mohammad Yeakub (2008)
The generation of intensive heat during grinding not only accelerates wheel wear but also impairs the machined surface by inducing tensile residual stresses, micro-cracks and thermal damage. The application of conventional cutting fluids does not help to remove these problems effectively, particularly under heavy cutting conditions. Moreover, conventional cooling methods produce environmental pollution and health hazards. One of the possible and potential techniques to overcome such problems is the application of cryogenic cooling where liquid nitrogen is used as a coolant The present work investigates the effects of cryogenic cooling using liquid nitrogen on chip feature, surface hardness, roughness, and wheel wear in grinding mild steel and stainless steel. The reduction of temperature at the cutting zone is found to produce favorable chip formation and relatively more surface roughness, but improves the wheel life and reduces surface burning. Furthermore, the technique is environmental friendly.